Sustainable technology of wastewater treatment by environmentally friendly modified natural sorbents for removal of nitrogen and phosphorus - Fediv, Iryna; Stepova, Kateryna; Šarko, Julita; Mažeikienė, Aušra (International Conference “Environmental Engineering”, 2023)
The work deals with the issues of nitrogen and phosphorus removal from wastewater. Natural and modified sorbents: zeolite, glauconite, and bentonite were tested under laboratory conditions. The studies used effluent from biological wastewater treatment that contained an average concentration of 2.2 mg/L of ammonium nitrogen; 7.6 mg/L of nitrate nitrogen and 8.7 mg/L of phosphate phosphorus concentration. Wastewater (0.5 L) was mixed with sorbents (5 g) at a speed of 200 revolutions per minute, then nitrogen and phosphorus concentrations in the solution were measured. Natural glauconite and bentonite removed 58–60% ammonium nitrogen, while modified sorbents show higher 63–70% ammonium nitrogen removal efficiency, respectively. Clinoptilolite removed ammonium nitrogen from wastewater with 76% efficiency. The tested sorbents removed nitrate nitrogen with 14–15% efficiency and phosphate phosphorus with 19–45% efficiency.